China's peripheral diplomacy: Repeating Europe's errors in dealing with the neighbourhood. Issue 3 (September 2019) - Sobol, Mor
The European Union (EU) and China are on a quest to establish themselves as global actors. Still, both powers first need to create a stable neighbourhood that will not threaten their interests. Consequently, in 2004 the EU launched the European Neighbourhood Policy (ENP), while in 2013 China's Peripheral Diplomacy (CPD) was introduced. Against this background, this article aims to conduct a comparative analysis of both initiatives. Specifically, as there is a wide agreement that the ENP has failed to generate any impact on the EU's periphery, the research question is: To what extent could the CPD transcend the problems of its European counterpart? The article posits that both policies are rather similar in their inability to strike the right balance between protecting core interests and acknowledging the neighbours' needs. Thus, it is likely that the CPD, just like the ENP, will remain a policy with big potential but without effective results.